Menopausal hormone therapy: what are the problems in the perception of Chinese physicians?. (4th July 2022) - Deng, Y.; Wang, W.; Zheng, Q.; Feng, Y.; Zou, Y.; Dong, H.; Tan, Z.; Zeng, X.; Zhao, Y.; Peng, D.; Yang, X.; Sun, A.
Abstract: Objective: This study aimed to investigate Chinese physicians' perception and attitudes toward menopausal hormone therapy (MHT). Methods: This nationwide online survey was conducted in China. Physicians registered in the WeChat groups of the Gynecological Endocrinology Committee of China's Maternal and Child Health Care Association received a message invitation to complete this anonymous online survey from April 2020 to July 2020. Physicians' knowledge of and attitudes toward MHT were surveyed. Results: In total, 4672 questionnaires were submitted; only completed questionnaires could be submitted. The message was sent to 6021 doctors, so the response rate was 77.6%. Overall, 77.9–92.9% of physicians knew the common indications and contraindications to MHT. Additionally, 90.6%, 85.4%, 80.7% and 37.5% of physicians thought that MHT would increase the risk of venous thrombosis, breast cancer, endometrial cancer and weight gain, respectively. In total, 58.1% of the physicians mistakenly believed that a sex hormone test was one of the necessary examinations to reassess MHT prescription during follow-up visits. We found that 68.5% of physicians would consider using MHT themselves or recommend MHT to their partners in the future, and 11.4% were currently using MHT. Conclusions: Most Chinese physicians have basic knowledge of MHT. Their misunderstandings about MHT mainly centered on the risks of endometrial cancer, weight gain and the necessary examinations during follow-up visits. These misunderstandings need to be clarified in future professional training programs.